Uzbekistan and the United States: Authoritarianism, Islamism & Washington’s Security Agenda by Shahram Akbarzadeh (London: Zed Books, 2005. 165 pages.) (American Journal of Islam and Society, 2006)
Uzbek president Islam Karimov has gotten away relatively easily with hisbrutal suppression of the Andijon uprising (May 13-14, 2005), in which thestate security forces opened fire on protesters and killed about 700 of them.Despite the fact that this book was written before this event, ShahramAkbarzadeh’s Uzbekistan and the United States: Authoritarianism,Islamism & Washington’s Security Agenda articulates quite well howKarimov came to the point where he could find the courage to becomeincreasingly authoritarian despite Uzbekistan’s bad record of human rightsabuses and failed democratic reforms. The author argues that Karimov’salready existing authoritarianism has intensified and yet has been relativelyignored as a result of his close cooperation with the United States in theAmerican-led “war-on-terror.” He argues that the common threat of Islamist extremism has brought the United States and Uzbekistan togetherand has become a pretext for the latter to continue its repressive policies,which have caused Uzbekistan’s human rights and democratization recordsto falter even further.Akbarzadeh takes the reader through a series of sociopolitical transformationsby which Karimov has sought to consolidate his power. Theseinclude the domestic restructuring of the Uzbek political system in the post-Soviet era; regional alignments and power struggles, most notably againstRussia; and, finally, Tashkent’s long-sought bilateral relations with theUnited States, which gained a whole new dimension after 9/11 and throughoutthe American-led “war on terror.” The author concludes that the cooperationbetween Tashkent and Washington in the fight against Islamistextremism and, consequently, the latter’s downplaying its concerns aboutdemocratic reforms in Uzbekistan, would only encourage Karimov to bemore repressive and less accountable toward the citizens of Uzbekistan.The book contributes to the understanding of political developments in thenewly independent states by probing the interaction between Uzbek domesticpolitics and the international political and security agendas ...